The Influence of Parents' Perceptions of Education on the Sustainability of Children's Formal Education in Punggur Village, Kubu Raya District - Imran Imran; Iwan Ramadhan; Riama Al Hidayah; Hadi Wiyono; Stella Prancisca (Universitas Dharma Wacana, 2022)
This study aimed to determine how much influence parents' perceptions of education have on the continuity of children's formal education in Punggur Village, Kubu Raya Regency. The method used in this study was quantitative descriptive, using data collection techniques, namely questionnaires, interviews and documentation. This study attempts to determine parents' perceptions about children's education to increase parental participation in the continuity of children's education. This study intends to provide solutions to all problems that occur in the form of input and as a reference for this perception in increasing the role and participation of parents in the world of education, especially in the Punggur Village area, Kubu Raya Regency